Strategiese bakens vir die wisselwerking tussen eenheid, verskeidenheid en roepingsvervulling in die plaaslike kerk - G. van Wyk; B. J. de Klerk (Acta Theologica)
Every local church, although part of a greater denomination, finds itself in a unique context with unique ministerial needs. It is of the utmost importance for every local church to be contextual in its ministry. To make this possible a Scriptural view of the interplay between the unity of the church, the diversity of the church and the fulfilment of the calling of the church, currently not existing, is a key factor. The primary goal of this article is to provide guidelines to churches to assure the contextualisation of their calling and ministerial strategy. Beacons were developed in the light of the Scriptural interplay and presented as guidelines for the local church.The beacons are, in short: 1. Identifying the unique context; 2. Ascertaining of the current interplay; 3. Ascertaining of the Scriptural interplay; 4. Breaking through traditions; 5. Creating balance in the interplay; 6. Ensuring unity in communal interest; 7. Ensuring diversity, not in own interest; 8. Accommodating each other.